Assessing the Awareness of Using Veterinary Medical Drugs Among Village Animal Health Workers in Battambang Province - Nget, Vibol; Morm, Sophany (Badan Penerbitan Fakultas Pertanian (BPFP), 2025)
AMR is a serious health issue in the 21st century as infections caused by resistant organisms become harder to treat, leading to longer illnesses, more hospital visits, and a higher risk of death. In parallel, it is also affecting Cambodia's health and economy. This study aims to understand rural veterinarians' knowledge, attitudes, and practices regarding antimicrobial resistance in a northern province of Cambodia. The target districts were purposefully chosen and include Battambang City, Sangkae District, Moung Russei District, and Bavel District. Village Animal Health Workers (VAHWs) were randomly selected and interviewed using a structured questionnaire. All respondents, all of whom were veterinarians, were male. Among them, 33% had completed primary education, while only 4% had completed higher education. The services provided by VAHWs and in treatment are not significantly different (P>0.05), with the majority of services being for cattle (100%), swine (71%), and buffaloes (7%). However, all veterinarians (100%) were aware of antimicrobial resistance, with 44% learning about it through training courses. Among these, 84% expressed concern, citing increased difficulty in treatment and diagnosis. Furthermore, 61% believed antibiotics could be used for prevention, while 26% used them to promote growth. It is concluded that antimicrobial resistance in Battambang is a serious concern. Therefore, VAHWs should be empowered through capacity-building, and relevant institutions should strengthen regulations governing the use of veterinary medicines to promote better practices. Additionally, the phrase 'use antibiotics with caution' should be included on packaging in Khmer script.